2016
DOI: 10.1152/jn.00227.2016
|View full text |Cite
|
Sign up to set email alerts
|

Shared and distinct retinal input to the mouse superior colliculus and dorsal lateral geniculate nucleus

Abstract: Our results suggest that the mouse superior colliculus (SC) has access to input from most of the retinal ganglion cells (RGCs) that innervate the dorsal lateral geniculate nucleus (dLGN). By comparison, a number of RGC types appear to innervate the SC but not the dLGN; these RGCs generally exhibit more transient responses and respond best to small stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(172 citation statements)
references
References 65 publications
7
165
0
Order By: Relevance
“…To determine whether Sox11 acts directly on RGCs to promote regeneration, we injected AAV2-FLEX-Sox11 into the vitreous bodies of vGlut2-Cre mice, in which Cre is expressed in RGCs selectively (Ellis et al, 2016), and subjected these mice to an optic nerve injury. We found that AAV-FLEX-Sox11 induced regeneration was comparable to those induced by non-conditional AAV-Sox11 (Figure S2D, S2E, as compared with Figure 1A, 1C).…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether Sox11 acts directly on RGCs to promote regeneration, we injected AAV2-FLEX-Sox11 into the vitreous bodies of vGlut2-Cre mice, in which Cre is expressed in RGCs selectively (Ellis et al, 2016), and subjected these mice to an optic nerve injury. We found that AAV-FLEX-Sox11 induced regeneration was comparable to those induced by non-conditional AAV-Sox11 (Figure S2D, S2E, as compared with Figure 1A, 1C).…”
Section: Resultsmentioning
confidence: 99%
“…2D). Although more than 30 classes of RGCs exist in nocturnal rodents only a subset innervate dLGN (Sanes & Masland, 2015; Baden et al, 2016; Ellis et al, 2016). This suggests that targeting mechanisms exist that guide some classes of RGC axons into dLGN and exclude others.…”
Section: Afferent Projections Of Retinorecipient Thalamic Nucleimentioning
confidence: 99%
“…In rodents, including mice, the SC is the primary target of the retina, with at least 85% of retinal ganglion cell output sent to the superficial layers of the SC (Ellis et al . ). Yet, although the SC is the largest visual area in the mouse brain, and a prominent model in developmental work (Huberman et al .…”
Section: Introductionmentioning
confidence: 97%